Jiwa dan Terapi Kognitif Perspektif Abu Zayd al-Balkhi - Muwafiqi, Erny Fitroh Nabila; Fazary, M Fakhry Asa; Soleh, Achmad Khudori (CV. Lentera Literasi Indonesia, 2025)
Cognitive discusses human development in thinking or the process of cognition or the process of knowing. During his cognitive development, if it is found that the process of managing information is not appropriate, then cognitive therapy begins to play a role. The purpose of this paper is to find out about mental and cognitive therapy from the perspective of Abu Zayd al Balkhi. The research method used is qualitative with literature study techniques by collecting scientifically designed references and references that are in tune with the research objectives. Data analysis used in this research is content analysis. The results of this study are 1) The soul aspect becomes part of the human physical condition which influences each other. Therefore, the quality of the soul depends on the individual in managing it. 2) A body that is healthy or unhealthy (sick) will experience balance and balance in the soul. 3) In carrying out cognitive therapy more emphasis on the quality of the therapeutic relationship as a fundamental thing, such as warmth, appropriate empathy and mutual truss.